2018
DOI: 10.1093/chromsci/bmy067
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Dexpanthenol, Lidocaine Hydrochloride, Mepyramine Maleate and their Related Substances by a RP-HPLC Method in Topical Dosage Forms

Abstract: The pharmaceutical combination of dexpanthenol (DPA), lidocaine hydrochloride (LIH) and mepyramine maleate (MAM) is used for their anti-allergic, anti-inflammatory, anti-pruritic, anesthetic and antiseptic properties. The present study was aimed to develop and validate a new, first and rapid high performance liquid chromatographic method for simultaneous determination of DPA, LIH and MAM in the presence of their stress-induced degradation products in pharmaceutical gel/fluigel formulations. The chromatographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…CUR is present in yellowish solution due to long intense wavelength absorption in the visible region [ 14 ]; therefore, it was analysed at 425 nm. On the other hand, DPA is a colourless liquid and does not exhibit strong UV–visible absorption; therefore, it must be quantified by using a low UV wavelength [ 12 , 15 ]. Accordingly, we analysed DPA at 200 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CUR is present in yellowish solution due to long intense wavelength absorption in the visible region [ 14 ]; therefore, it was analysed at 425 nm. On the other hand, DPA is a colourless liquid and does not exhibit strong UV–visible absorption; therefore, it must be quantified by using a low UV wavelength [ 12 , 15 ]. Accordingly, we analysed DPA at 200 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies have reported HPLC methods to determine DPA or CUR independently. However, there are some previously published works describing the simultaneous determination of DPA and other compounds such as lidocaine, mepyramine or resorcinol in different formulations [ 12 , 20 ]. These methods presented higher LOD and LOQ values than the ones reported in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Additionally, other validated methods exist for determining the drug in polymeric matrices, [26][27][28] plasma, 29,30 and in new topical dosage forms. 25,[31][32][33] Methods for the quan-tication of TZ, on the other hand, were described for analysing the drug alone, 34,35 concurrently with other drugs like muscle relaxants, 36 analgesics, [37][38][39] and anti-inammatories, [40][41][42][43][44][45][46][47][48] and from pharmaceutical formulations. 2,38,42,[44][45][46][47][48][49][50][51] Moreover, a method has been described for detecting TZ in skin deposition 52 and plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive study of the literature [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], it was discovered that many analytical techniques for LID estimation had been published, including ultraviolet, high performance liquid chromatography, RP-HPLC, HPLC-MS/MS, etc. Methods for analysing DIL had been documented, including Ultra violet, high performance liquid chromatography, high performance thin layer chromatography, etc.…”
Section: Introductionmentioning
confidence: 99%